Interface entre a educação e saúde: caderno orientativo de primeiros socorros - Parente, Ednei Pereira (2023)
Federal educational institutions, within the scope of professional and technological education, being a full-time environment, the student occupies most of his/her time in the institution, which may, at a certain moment, enable the occurrence of accidents in the academic environment, thus requiring immediate first aid care by a teacher or any employee of the institution. The study presented herein has a its theme: Interface between education and health and how knowledge about first aid can contribute to on-site assistance. The objective of the research is to evaluate the importance of developing actions in the area of first aid that contribute to pedagogical teaching. To meet the general objective, the specific objectives were: to present, through theoretical referential, the legal framework of EPT and the current legislations in the health area in relation to first aid; to show, through theoretical contributions, the importance and applicability of PS techniques as pedagogical practice; to identify, through in loco research, the previous knowledge of teachers in relation to the theme; to propose, as an educational product, a first aid orientation booklet, in order to multiply knowledge and practical actions to be taken when facing situations that require basic knowledge of first aid techniques. The research is justified since all the knowledge acquired in teacher training enables an improvement in the teaching learning process, thus contributing to the teacher's pedagogical practice. The research guiding questions were: does continuing education contribute to the improvement of the pedagogical practice of the process? Does knowledge of current legislation regarding first aid in educational institutions enable actions/measures to be applied to clinical emergencies and traumatic emergencies in the academic community? The theoretical contribution was based on authors who deal with EFA, the importance of the interface between education and health, as well as the current legislation. The methodological approach was based on action research with a qualitative approach. As for the means, the research was field research, the data collection instruments were given through the application of three instruments: the application of semi-structured questionnaires; pre-intervention survey. Next, a first aid workshop would have taken place, followed by the second post-intervention questionnaire with the professionals assigned to the Coari Campus in person, via Google Forms, (in case they continued the social distancing because of Covid-19), preceded by a literature review and document analysis. Content analysis was used, under the constructive-interpretative perspective presented by González Rey (2002). The findings were organized in the thematic perspective related to the "inferences and interpretations of the results obtained in the analysis of the information" (BARDIN, 2016). The results of the research guided the preparation of the first aid orientation booklet of the educational product. It is concluded that there are cases of accidents and risks, ignorance of first aid techniques of professional and technological education professionals to provide the first care to the victim, and current legislation.